Developing a federated data governance framework: evolving from minimum viable structures towards governance maturity - Kokkonen, Maj (My University, 2026)
The importance of data governance has been increasingly recognized within organizations in recent years. Data is an important business asset across multiple organizational functions, and its effective utilization as a strategic asset can lead to sustainable competitive advantage. As an organization’s data landscape grows, data can become fragmented across business units, applications, legacy systems, and databases. Data fragmentation can lead to a decrease in data quality, negatively affecting business processes, reporting, and decision-making. Furthermore, data legislation (e.g. EU Data Act, GDPR) is increasingly created to ensure that organizations collect and utilize data in a compliant way. While data governance is widely recognized as an organization-dependent concept, existing data governance literature and frameworks are often aimed towards companies with high organizational maturity and resource availability. Most literature remains on a conceptual level, without providing practical direction on data governance development within the organizational environment. These factors combined make the existing data governance frameworks difficult to implement in organizations at early stages of governance development. This thesis addresses this gap by designing a data governance framework for a global organization with a large data ecosystem, but low governance maturity and limited resources. The thesis utilizes Design Science Research (DSR) methodology, that is used to develop and evaluate a four-stage federated data governance framework that enables gradual progression from a minimum viable governance structure to a fully mature governance model. The framework incorporates modern best governance practices from the academic knowledge base, incorporating principles of agility and data mesh. Organizational applicability is ensured through empirical data collection, including interviews, workshops, and company documentation. The DSR methodology involves multiple iterative design cycles and evaluations, ensuring academic rigor and organizational applicability. The findings confirm that the proposed framework is both feasible and implementable, effectively addressing the organization’s real-world governance challenges. The staged, incremental approach reduces the threshold for governance adaptation and reduces complexity. From a scientific perspective, the thesis contributes to existing data governance knowledge base by operationalizing academic principles and best practices in a real-world context. Further, it illustrates the DSR process that can be useful to and replicated by other researchers and practitioners. While the model and research process can be applied by other organizations and researchers, further research is needed to evaluate the implementation of the framework as well as its generalizability.

Datanhallinnan (eng. data governance) merkitys on viime vuosina tunnistettu yhä laajemmin eri organisaatioissa. Data on yrityksille tärkeä liiketoiminnallinen resurssi ja sen strateginen hyödyntäminen voi luoda kestävää kilpailuetua eri organisaatioille. Organisaatioiden dataympäristön kasvaessa data voi hajaantua eri liiketoimintayksikköihin, sovelluksiin, vanhoihin järjestelmiin ja tietokantoihin. Tämä voi heikentää datan laatua, vaikuttaen negatiivisesti liiketoimintaprosesseihin, raportointiin ja päätöksentekoon. Datalainsäädäntö myös kehittyy jatkuvasti (esim. EU:n Data Act, GDPR), jolla pyritään varmistamaan organisaatioiden säädöstenmukainen datankeruu ja -hyödyntäminen. Vaikka datanhallinta tunnistetaan luonteeltaan organisaatiokohtaiseksi, suurin osa akateemisesta kirjallisuudesta on suunnattu korkean organisaatiomaturiteetin yrityksille, joilla on suuri määrä resursseja käytettävissään. Suuri osa kirjallisuudesta pysyttelee myös konseptuaalisella tasolla, tarjoamatta konkreettisia ohjeita datanhallinnan kehittämisestä organisaatioympäristössä. Näiden tekijöiden vuoksi nykyiset akateemiset viitekehykset ovat suurelta osin vaikeasti sovellettavia organisaatioihin, joiden datanhallinnan maturiteetti- ja resurssitaso on alhainen. Tämän pro gradu -tutkielman tavoitteena on suunnitella datanhallinnan viitekehys globaalille yritykselle, jolla on laaja dataympäristö, mutta matala maturiteetti- ja resurssitaso. Tämä pro gradu -tutkielma hyödyntää Design Science Research (DSR) -metodologiaa, jota hyödynnetään nelitasoisen, federatiivisen datanhallinnan viitekehyksen kehittämisessä ja arvioinnissa. Viitekehys mahdollistaa datanhallinnan asteittaisen etenemisen vähimmäistasoisesta hallintarakenteesta kohti korkean maturiteettitason hallintamallia. Viitekehys perustuu akateemisen kirjallisuuden parhaisiin käytäntöihin, hyödyntäen esimerkiksi ketteriä (eng. agile) ja data mesh -periaatteita. Viitekehyksen soveltuvuus kohdeorganisaatioon varmistetaan empiirisellä aineistolla, kuten haastatteluilla, työpajoilla ja sisäisellä dokumentaatiolla. DSR-metodologia sisältää useita iteratiivisia suunnittelu- ja arviointisyklejä, jotka takaavat tutkimuksen akateemisen tarkkuuden ja organisatorisen soveltuvuuden. Tutkimuksen löydökset vahvistavat, että suunniteltu viitekehys on sekä toteuttamiskelpoinen että valmis implementoitavaksi kohdeyritykselle. Se ratkaisee organisaation datanhallinnan haasteet. Vaiheittainen lähestymistapa madaltaa kynnystä koskien hallintamallin käyttöönottoa. Tieteellisestä näkökulmasta tutkielma täydentää olemassa olevaa datanhallinnan kirjallisuutta operationalisoimalla olemassa olevia akateemisia periaatteita ja parhaita käytäntöjä reaalimaailman kontekstissa. Lisäksi tutkimus kuvaa käytännönläheisesti DSR-prosessin, joka voi olla hyödyllinen ja toistettavissa muiden tutkijoiden ja harjoittajien toimesta. Vaikka viitekehys ja tutkimusprosessi voivat olla sovellettavissa myös muissa organisaatioissa ja tutkimuksissa, jatkotutkimusta tarvitaan viitekehyksen käyttöönoton arvioimiseksi, kuten myös sen yleistettävyyden varmistamiseksi.
Keywords: data governance, agile governance, agile data governance, federated data governance, design science research, information systems science, data governance, datanhallinta, ketterä datanhallinta, federatiivinen datanhallinta, design science research, tietojärjestelmätiede